Analysis of Smash Shot Accuracy in Badminton Extracurricular Participants at Junior High School 3 Batumandi Balangan Regency South Kalimantan - Hendriansyah; Abd Hamid; Mita Erliana (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to analyze the accuracy level of smash shots in badminton extracurricular participants at Junior High School 3 Batumandi, Balangan Regency. This research used a descriptive quantitative method with a population and sample of 15 participants (total sampling). Data were collected using a smash accuracy test, where each participant performed 20 smash attempts evaluated based on the landing position of the shuttlecock using a scoring system ranging from 0 to 5 points. The results showed that 1 participant (6.7%) was in the very good category, 2 participants (13.3%) in the good category, 3 participants (20%) in the fair category, 8 participants (53.3%) in the poor category, and 1 participant (6.7%) in the very poor category. The conclusion of the study is that the accuracy level of smash shots among badminton extracurricular participants at Junior High School 3 Batumandi is categorized as poor. This is mainly because most participants performed smashes from an unprepared position and did not execute preliminary footwork steps.